THE ESTABLISHMENT OF THE PRINCIPLES OF THE U.S. "THE SPREAD OF DEMOCRATIC IDEAS" FROM WILSONISM TO THE "EISENHOWER DOCTRINE" (Journal of Oriental Studies, 2016)
This article considers the formation of U.S. foreign policy and the development of concepts and doctrines aimed at promoting "democratic ideas" at the international level.
Keywords: USA; USSR; Middle East; foreign policy doctrine; international relations